2020
DOI: 10.1158/1078-0432.ccr-19-3523
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Pathway Inhibition Overcomes Adaptive Feedback Resistance to KRASG12C Inhibition

Abstract: ◥Purpose: Although KRAS represents the most commonly mutated oncogene, it has long been considered an "undruggable" target. Novel covalent inhibitors selective for the KRAS G12C mutation offer the unprecedented opportunity to target KRAS directly. However, prior efforts to target the RAS-MAPK pathway have been hampered by adaptive feedback, which drives pathway reactivation and resistance.Experimental Design: A panel of KRAS G12C cell lines were treated with the KRAS G12C inhibitors ARS-1620 and AMG 510 to ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
379
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(398 citation statements)
references
References 52 publications
19
379
0
Order By: Relevance
“…Furthermore, PTPN11 KO or SOS1 knockdown had biological and biochemical consequences similar to those of SHP099. Our results are consistent with, and strengthen, previous studies of the effects of SHP2 modulation on G12C-I inhibitor action (22,(38)(39)(40)(41). Fig S3 I-J) revealed that PTP activity is essential, whereas C-terminal tyrosine residues play a modulatory role, in adaptive resistance to G12C-Is.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, PTPN11 KO or SOS1 knockdown had biological and biochemical consequences similar to those of SHP099. Our results are consistent with, and strengthen, previous studies of the effects of SHP2 modulation on G12C-I inhibitor action (22,(38)(39)(40)(41). Fig S3 I-J) revealed that PTP activity is essential, whereas C-terminal tyrosine residues play a modulatory role, in adaptive resistance to G12C-Is.…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports (and our unpublished observations; see Results) show that KRAS G12C -mutant cancer cell lines treated with G12C-Is also develop adaptive resistance (22,(38)(39)(40)(41). These studies reported that adaptive response to G12C-Is could be minimized by combining G12C-I with RTK or SHP2 inhibitors (22,38,40,41). Some of these findings were validated in human cell-derived (CDXs) or patient-derived xenografts (PDXs) (39).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the case of non-small cell lung cancer (NSCLC), KRAS mutations occur predominantly in codons 12 and 13, and most frequent variants including G12C, G12V, and G12D (9,17). Recently, a series of compounds targeted KRAS-G12C variant were developed and achieved promising effects on preclinical experiments and phase I clinical trials (18)(19)(20). However, the clinical bene ts especially for other KRAS variants remain clari ed.…”
Section: Introductionmentioning
confidence: 99%